Comunicação pública, desenhos institucionais e gestão compartilhada: a interlocução entre poder público e cidadãos na proposta da Prefeitura de Belo Horizonte - Laura Nayara Pimenta (2015)
This work understand how the communicative interactions of a community from occupation - Vila Jardim do Vale turns it in a public able to participate, to increase their civic power and thus influence the decision of a public authority's, considering a context of shared management. For this, we understand that this public communication process in this proposal management, becomes a complex of large and specific interactions that are not mutually exclusive, however, permeate, because at the same time that these dialogues demand an opening, visibility and publicity of debates, they also conform to the design of participative spaces, putting on the institutions. The institutional design concept is important to understand the potential and limitations of the participative forms, particularly refer to three main aspects: who participates; how decisions are made and how these are linked to the public policy. Although the proposal for shared management self-respecting the establishment of channels that enable a joint effort between state and civil society, we must consider that, currently, these bodies have institutional designs that give an outline to interactions between government and citizens, and especially , to dialogues with the various community-based training organized in the city. Therefore, to achieve our goal, we use systematic observations, interviews and document analysis, in order to understand the institutional designs present in the shared management model advocated by the municipality of Belo Horizonte, showing their normativities and the public communication process establishing. Also grasp the communicative interactions in community mobilization village process and its links with other neighborhood claim networks to cope with an institutional design and try to influence the decision making of the government